6-(4-Methylphenyl)-1,3,5-triazine-2,4-diamine–4-methylbenzoic acid (1/1) - Kaliyaperumal Thanigaimani; Suhana Arshad; Ibrahim Abdul Razak; Duraisamy Makeshvaran; Kasthuri Balasubramani (Acta Crystallographica Section E, 2013)
The 4-methylbenzoic acid molecule of the title adduct, C10H11N5·C8H8O2, is approximately planar with a dihedral angle of 6.3 (2)° between the carboxylic acid group and the benzene ring. In the triazine molecule, the plane of the triazine ring makes a dihedral angle of 29.2 (2)° with that of the adjacent benzene ring. In the crystal, the acid and base molecules are linked via N—H...O and O—H...N hydrogen bonds with an R22(8) motif, and the acid–base pairs are further connected via N—H...N hydrogen bonds with R22(8) motifs, forming a supramolecular ribbon along [101]. Between the tapes, a weak C—H...π interaction is observed.